Clinical-Laboratory Features, Diagnostics of Bollard Pyelonephritis during the Covid-19 Pandemic (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
During the years 2019-2021, in connection with the pandemic of the new viral SARS-CoV-2 (COVID-19) infection, which spread among mankind, many scientific researches are being conducted on the diagnosis, treatment and prevention of the Covid- 19 virus . It was observed that the incidence of Covid-19 infection among children increased significantly during 2021. Children with a premorbid background can be included in the group of children who are prone to severe cases of COVID-19 (lung diseases, Kawasaki disease, various immunodeficiency conditions, kidney diseases, etc.). It is known that children over 5 years of age are most often affected. It is said that the disease is often asymptomatic, but children with kidney disease have a severe and protracted disease course. The epidemiology of the COVID-19 disease among children and the pathogenetic mechanisms of damage to various organs, morphology, clinical course, laboratory diagnostics, treatment and rehabilitation have not been fully resolved in pediatric practice.